What’s new for the clinician? - Excerpts from and summaries of recently published papers - Yengopal, Veerasamy (South African Dental Journal, 2021)
The World Health Organization (WHO) considers breast milk as the best source of nourishment for infants. Although exclusive breastfeeding is recommended up to 6 months of age, globally only 40% of children under this age are exclusively breastfed and this is mainly due to negative breastfeeding experiences. There are many different causes for negative breastfeeding experiences such as poor weight gain, necessitating supplementation, poor latch, maternal nipple pain, and oral restrictions like a tongue-tie (ankyloglossia) and/or lip-tie. Ankyloglossia (either the decrease in mobility for the tongue by classic anterior tongue-tie or a submucosal restriction, a posterior tongue-tie) and a superior tethered labial frenulum can cause altered latch and sucking mechanics. Studies have shown that a frenotomy, if adequately performed, can improve breastfeeding scores and relieve nipple pain with little or no serious complications.